Risk Mitigation Strategies for Fish Shredded Production Due the Impact of Covid-19 Pandemic - Ramli Ramli; Siti Nur Aisyah Jamil; Ismi Jasila (Enrichment : Journal of Management, 2022)
Micro and small businesses that produce variants of fish shredded products are faced with business uncertainty and losses due to the risks faced in the production process due to the impact of the covid-19 pandemic. The purpose of this study is to find out the risko variables and risk mitigation strategies for fish shredded production due to the impact of the Covid-19 pandemic. The analysis methods used are Failure Mode Effect Analysis (FMEA) and Analytical Hierarchy ProcessAHP). The results showed that the highest risks were rising raw material prices, fluctuating and uncertain production activities, and demand is fluctuating and tending to decline. Priority strategies alternative for minimizing risk are reformatting partnerships with raw material suppliers, improving inventory management, and planning and forecasting demand.